USE OF CASHEW BARK EXUDATE GUM IN THE PREPARATION OF 4 % LIDOCAINE HCL TOPICAL GELS - Hasnain, M. Saquib; Rishishwar, Poonam; Ali, Sadath (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of the current work was to prepare and evaluate ex vivo skin permeation of cashew bark exudate gum based 4 % lidocaine HCl topical gels. Methods: In the current work, 4 % lidocaine HCl topical gels were prepared by using different concentrations of cashew bark exudate gum, HPMC K4M, lidocaine HCl, methyl paraben (as preservative) and glycerin (as plasticizer). The formulated topical gels were evaluated for pH, viscosity, and ex vivo skin permeation through excised porcine ear skin membrane. Results: The pHs of these formulated 4 % lidocaine HCl topical gels were found within the range of 6.04±0.02 to 6.52±0.04; whereas, the viscosities were measured within the range, 4.38±0.02 x 106to 4.74±0.04 x 106 cps. Sustained ex vivo permeation of lidocaine was measured over 7 h. Highest ex vivo permeation flux was measured when 0.1 % menthol was incorporated as a permeation enhancer. It was also higher than that of the marketed 4 % lidocaine HCl topical gel. The stability study by freeze thaw cycle method revealed physically stable gels without the occurrence of syneresis. Conclusion: The results clearly indicate a promising potential of the use of cashew bark exudate gum as a gelling material with HPMC K4M to prepare 4 % lidocaine HCl topical gels of good skin permeation capability